2022
DOI: 10.3390/molecules27134152
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Volatilomes of Livestock Dung Drive Preference of the Dung Beetle Bubas bison (Coleoptera: Scarabaeidae)

Abstract: Volatile cues can play a significant role in the location and discrimination of food resources by insects. Dung beetles have been reported to discriminate among dung types produced by different species, thereby exhibiting behavioral preferences. However, the role of volatile organic compounds (VOCs) in dung localization and preference remains largely unexplored in dung beetles. Here we performed several studies: firstly, cage olfactometer bioassays were performed to evaluate the behavioral responses of Bubas b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Acetic acid has been related to high-dose N fertilization in Brassica napus plants and serves as a potential attractant of Meligethes aeneus and D. melanogaster [11,17]. Butyric acid is a key attractant of pests such as Holotrichia paralela and Bubas bison [20,21]. A compound induced by herbivory, 2-octanol, has been reported as an attractant of Spilosoma obliqua [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetic acid has been related to high-dose N fertilization in Brassica napus plants and serves as a potential attractant of Meligethes aeneus and D. melanogaster [11,17]. Butyric acid is a key attractant of pests such as Holotrichia paralela and Bubas bison [20,21]. A compound induced by herbivory, 2-octanol, has been reported as an attractant of Spilosoma obliqua [22].…”
Section: Discussionmentioning
confidence: 99%
“…In Camellia sinensis plants, 1,3-benzenedicarboxylic acid has been related to N fertilization doses and infestation of the aphid Toxoptera aurantii [23]. The most abundant compound in CF was phenol, which acts as an attractant of beetles of the species B. bison [21].…”
Section: Discussionmentioning
confidence: 99%
“…The key volatile used by dung beetles is a shikimic product, p-cresol (Dormont et al, 2010), though there are a wide array of VOCs with combinations, which are as attractive as fresh dung (Frank et al, 2017). Volatiles released by dung vary by animal species (Dormont et al, 2004(Dormont et al, , 2010Perera et al, 2022) and the presence of other insects in the dung (Dormont et al, 2010), but only a single study demonstrates that diet of animals influences the volatile composition released (Perera et al, 2022). Specifically, the dung beetle Bubas bison (L., 1767) preferred dung from horses fed pasture compared with lucerne hay-fed animals (Perera et al, 2022).…”
Section: Reproductionmentioning
confidence: 99%
“…Volatiles released by dung vary by animal species (Dormont et al, 2004(Dormont et al, , 2010Perera et al, 2022) and the presence of other insects in the dung (Dormont et al, 2010), but only a single study demonstrates that diet of animals influences the volatile composition released (Perera et al, 2022). Specifically, the dung beetle Bubas bison (L., 1767) preferred dung from horses fed pasture compared with lucerne hay-fed animals (Perera et al, 2022). How pasture diets influence the volatiles released by cattle dung and the colonisation of cattle dung-by-dung beetles in the field is unknown and warrants further investigation.…”
Section: Reproductionmentioning
confidence: 99%
“…Recently, it has been shown that dung beetle olfactory systems can recognize and discriminate amongst various VOCs in the environment. For example, several studies have reported variation in attraction and clear trophic preferences to dung by dung beetles under a range of field and laboratory conditions [6,33,[35][36][37][38][39]. Sladecek et al [40] present empirical evidence as to how the temporal variation of volatiles emitted from cow dung pats influences the community dynamics of dung inhabitants, mainly beetles and flies.…”
Section: Introductionmentioning
confidence: 99%